Анализ наноразмерных металлических слоев Zr/Nb после протонного облучения - Лаптев Р. С. Роман Сергеевич; Ломыгин А. Д. Антон Дмитриевич; Кобец А. Г. Андрей Геннадьевич; Siemek K. Kshishtof (2022, 2022)
Заглавие с экрана